Rethinking knee injury prevention strategies: joint-by-joint training approach paradigm versus traditional focused knee strengthening - Dhahbi, Wissem; Materne, Olivier; Chamari, Karim (Biology of Sport, 2025)
Knee injuries remain a significant challenge in competitive sports, impacting athletic performance, long-term joint health, and healthcare resource utilization. Traditional prevention strategies often focused primarily on strengthening the knee itself. However, emerging evidence supports a joint-by-joint training approach (JBJTA), emphasizing the interconnected kinetic chain, particularly the trunk, hips, ankles, and feet. This commentary explores the potential of JBJTA in knee injury prevention by enhancing hip and ankle mobility, trunk and foot stability, and proprioception. The JBJTA posits that optimal joint function and adaptability across the kinetic chain contribute to reduced knee stress and improved dynamic stability. Limited hip range of motion (ROM) and ankle dorsiflexion are associated with altered mechanics, such as increased knee valgus, which increases the risk of anterior cruciate ligament (ACL) injuries. Additionally, foot stability and proprioception are crucial for dynamic balance and neuromuscular control, further mitigating knee injury risk. Furthermore, we highlight the importance of the JBJTA for biomechanical knee load redistribution, optimizing force distribution throughout the lower limb to alleviate knee stress. The approach enhances lower limb alignment, shock absorption, and efficient force transfer, contributing to reduced knee valgus and overall injury risk. The JBJTA offers a comprehensive strategy for knee injury prevention by addressing the interdependence of the kinetic chain. This paradigm shift from isolated knee strengthening to a holistic approach promises improved performance and long term musculoskeletal health for athletes. We call for future research to rigorously evaluate the efficacy of this approach in diverse athletic populations.